2013
DOI: 10.1080/17470919.2013.835279
|View full text |Cite
|
Sign up to set email alerts
|

The male advantage in child facial resemblance detection: Behavioral and ERP evidence

Abstract: Males have been suggested to have advantages over females in reactions to child facial resemblance, which reflects the evolutionary pressure on males to solve the adaptive paternal uncertainty problem and to identify biological offspring. However, previous studies showed inconsistent results and the male advantage in child facial resemblance perception, as a kin detection mechanism, is still unclear. Here we investigated the behavioral and brain mechanisms underlying the self-resembling faces processing and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 80 publications
2
16
0
Order By: Relevance
“…The beloved faces as non-novel stimuli decreased the face identity conflict (Langeslag et al, 2007). Wu et al (2013) found males showed smaller N2 amplitudes for self-resembling child faces, which may reflect the conflict monitoring of the ACC during kin detection. In previous studies regarding facial expressions, the N2 was found to be larger for neutral faces as compared to faces with emotional expressions.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The beloved faces as non-novel stimuli decreased the face identity conflict (Langeslag et al, 2007). Wu et al (2013) found males showed smaller N2 amplitudes for self-resembling child faces, which may reflect the conflict monitoring of the ACC during kin detection. In previous studies regarding facial expressions, the N2 was found to be larger for neutral faces as compared to faces with emotional expressions.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, the most negative peak was defined as being between 200 and 300 ms for the fronto-central N2, and the peak amplitudes and latencies were measured at this time window for the N2 component. Consistent with the analyzing method in previous studies, the peak amplitudes were analyzed for N2 component (e.g., Chen et al, 2012;Wu et al, 2013). Additionally, regarding the late positive potential (LPP), since in many participants, the LPP peak was not easily discernible, the analysis was based on the mean amplitude calculated between 450 and 600 ms (based on the grand-average waveforms).…”
Section: Electrophysiological Recording and Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…Previous findings indicated that LPC or P3 was highly sensitive to the process of stimulus evaluation, response execution [33] and motivational significance [16]. Wu and Yang et al [28] suggested that LPC may reflect self-referential processing in kin detection.…”
Section: Discussionmentioning
confidence: 99%
“…Kinship verification has been traditionally studied in psychology and neuroscience aiming at understanding the resemblance of faces of the same family [1,2,3]. To the best of our knowledge, the first attempt to conduct automatic kinship verification based on face images is described in the work of Fang et al [4].…”
Section: Related Workmentioning
confidence: 99%